A Effect of Varying Levels of Kidney Stone Leaf (Phyllanthus amarus) Meal on Broiler Chickens Performance: Effect of Varying Levels of Kidney Stone Leaf (Phyllanthus amarus) Meal on Broiler Chickens Performance - Sudik David Samuel (Jurnal Agro Veteriner, 2026)
This research investigated the impact of kidney stone leaf meal on the performance of broiler chickens. A total of 200 one-day-old Ross 308 chicks were randomly distributed into the five treatments, each consisting four replicates. Water and feed were supplied ad libitum for 45 days. Weight gain was (P<0.05) higher in day 24 at 5% KSLM, and day 45 in 5% and 7.5% KSLM, and lower in 10% KSLM while no (P>0.05) in feed intake. Again, 5% and 7.5% KSLM (P<0.05) had best FCR and livability. The 2.5%, 5%, and 7.5% KSLM (P<0.05) showed higher de-feathered and carcass weights, but higher breast weight in 5% and 7.5% KSLM. At day 45, intestinal weights (P<0.05) increased with increase KSLM, while gizzard, lungs, kidneys, crop, liver, and spleen were (P>0.05) unaffected. White blood cells, lymphocytes, and monocytes were (p<0.05) higher in 7.5% and 10% KSLM. Total protein and globulin were (P<0.05) similar in all the treatments except 10% KSLM. The 10% KSLM also showed (P<0.05) increased AST and ALT, and lower cholesterol. The conclusion drawn is that 5–7.5% KSLM can enhance performance of broiler, and limiting to 5% is advisable to improve immune system